Prevalence and Types of Coinfections in Sleeping Sickness Patients in Kenya (2000/2009) - J. M. Kagira; N. Maina; J. Njenga; S. M. Karanja; S. M. Karori; J. M. Ngotho (Journal of Tropical Medicine)
The occurrence of coinfections in human African trypanosomiasis (HAT) patients was investigated using a retrospective data of hospital records at the National Sleeping Sickness Referral Hospital in Alupe, Kenya. A total of 31 patients, 19 males and 12 females, were diagnosed with HAT between the years 2000 and 2009. The observed co-infections included malaria (100%), helminthosis (64.5%), typhoid (22.5%), urinary tract infections (16.1%), HIV (12.9%), and tuberculosis (3.2%). The species of helminthes observed included Ancylostoma duodenale (38.7%), Ascaris lumbricoides (45.7%), Strongyloides stercoralis (9.7%), and Taenia spp. (3.2%). The patients were also infected with Entamoeba spp. (32.3%) and Trichomonas hominis (22.6%) protozoan parasites. The main clinical signs observed at the point of admission included headache (74.2%), fever (48.4%), sleep disorders (45.2%), and general body pain (41.9%). The HAT patients were treated with suramin (early stage, 9/31) and melarsoprol (late stage, 22/31). In conclusion, the study has shown that HAT patients have multiple co-infections which may influence the disease pathogenesis and complicate management of HAT.